2018
DOI: 10.1038/s41598-018-35799-1
|View full text |Cite
|
Sign up to set email alerts
|

Complex role of miR-130a-3p and miR-148a-3p balance on drug resistance and tumor biology in esophageal squamous cell carcinoma

Abstract: miRNAs play a crucial role in cancer development and progression. However, results on the impact of miRNAs on drug sensitivity and tumor biology vary, and most studies to date focussed on either increasing or decreasing miRNA expression levels. Therefore, the current study investigated the role of different expression levels of miR-130a-3p and miR-148a-3p on drug resistance and tumor biology in four esophageal squamous cell carcinoma cell lines. Interestingly, up- and downregulation of both miRNAs significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…For example, gain of miR‐241‐3p expression enhanced sensitivity of ESCC cells to cisplatin, whereas loss of miR‐445‐3p had a similar effect . It was also reported that modulation of miR‐130a‐3p and miR‐148a‐3p in both directions increased the sensitivity of ESCC cells to 5‐FU and cisplatin . We found that ectopic overexpression of miR‐377, which targeted CD133 and suppressed cancer stemness, had a chemosensitizing effect on ESCC cells .…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…For example, gain of miR‐241‐3p expression enhanced sensitivity of ESCC cells to cisplatin, whereas loss of miR‐445‐3p had a similar effect . It was also reported that modulation of miR‐130a‐3p and miR‐148a‐3p in both directions increased the sensitivity of ESCC cells to 5‐FU and cisplatin . We found that ectopic overexpression of miR‐377, which targeted CD133 and suppressed cancer stemness, had a chemosensitizing effect on ESCC cells .…”
Section: Introductionsupporting
confidence: 65%
“…Despite 5‐FU being an antimetabolic agent widely used in treating gastrointestinal cancers, the response rate of esophageal carcinoma to 5‐FU is only 15% . Emerging evidence indicates that miRNAs are associated with chemoresistance, but relatively few miRNAs were experimentally validated to have the ability to regulate the sensitivity of ESCC cells to 5‐FU treatment . Our present study found that miR‐338‐5p was underexpressed in 5‐FU‐resistant ESCC cells, and that ectopic overexpression of miR‐338‐5p in these cells could increase their sensitivity to 5‐FU treatment both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 47%
“…A previous report showed that Spatholobi Caulis tannin mediates several related circRNAs to suppress cell proliferation and promote apoptosis in cervical cancer [32]. In ESCC, ncRNAs have been suggested to play roles as oncogenes or tumor suppressors to regulate ESCC proliferation, apoptosis, epithelial-mesenchymal transition (EMT), metastasis, chemotherapy, or radiotherapy [33][34][35][36][37]. Additionally, several ncRNAs have been observed to serve as prognostic markers in patients with ESCC [5,38].…”
Section: Role Of Non-coding Rnas In Escc Progressionmentioning
confidence: 99%
“…However, when miR-148a-3p was downregulated, BIM was observed to be noticeably upregulated compared to the upregulation of BCL2. Furthermore, miR-130a-3p showed similar regulatory effects for BCL2 and X-linked inhibitor of apoptosis protein (XIAP) [34]. Balancing the regulation of several target genes is critical for an efficient response of miRNAs towards chemotherapy in ESCC.…”
Section: Non-coding Rnas Influence Chemoresistance and Radioresistancmentioning
confidence: 99%
See 1 more Smart Citation